2023
DOI: 10.3390/molecules28135133
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Copper Ions on the Activity of Antibiotic Drugs

Abstract: Copper (Cu) is an essential trace metal and its concentration in body plasma is tightly regulated. An increase in Cu concentration in body fluids is observed in numerous pathological conditions, including infections caused by microorganisms. Evidence shows that Cu ions can impact the activity of antibiotics by increasing efficiency or diminishing/neutralizing antibiotic activity, forming complexes which may lead to antibiotic structure degradation. Herein, we represent the evidence available on Cu–antibiotic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“… 20 Furthermore, it has recently been pointed out that Cu + and Cu 2+ have a significant impact on antibiotic activity. 23 There is growing interest in Cu 2+ complexes, as it has been shown that they can prevent or even reverse antimicrobial resistance to classical antibiotics. 23 26 To date, there appear to be few studies on in vitro to in vivo translation, which is attributed to the lack of knowledge of the molecular mechanisms underlying Cu 2+ –antibiotic interactions under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 Furthermore, it has recently been pointed out that Cu + and Cu 2+ have a significant impact on antibiotic activity. 23 There is growing interest in Cu 2+ complexes, as it has been shown that they can prevent or even reverse antimicrobial resistance to classical antibiotics. 23 26 To date, there appear to be few studies on in vitro to in vivo translation, which is attributed to the lack of knowledge of the molecular mechanisms underlying Cu 2+ –antibiotic interactions under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 23 There is growing interest in Cu 2+ complexes, as it has been shown that they can prevent or even reverse antimicrobial resistance to classical antibiotics. 23 26 To date, there appear to be few studies on in vitro to in vivo translation, which is attributed to the lack of knowledge of the molecular mechanisms underlying Cu 2+ –antibiotic interactions under physiological conditions. 23 So far, the exact mechanism for bacterial damage caused by Cu 2+ has not been fully explained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation